2020
DOI: 10.1186/s12885-020-07475-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and imaging characteristics of primary hepatic sarcomatoid carcinoma and sarcoma: a comparative study

Abstract: Background Primary hepatic sarcomatous carcinoma (PHSC) and primary hepatic sarcoma (PHS) are rare malignancies with frequent overlap in both the clinic and radiology. No comparative study of these tumors for the restricted cases has previously been undertaken. The purpose of our study was to analyze the clinical and imaging features of PHSCs and PHSs, with an emphasis on particularities and similarities through a comparison of the two tumors. Methods We retrospectively analyzed the clinical and imaging feat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…This was not significantly different from the mean overall survival (4 months) of patients treated with symptomatic and supportive care. Studies have reported that HSCs are hypovascular tumors, [29] and TACE is a risk factor associated with poor prognosis. [30] For patients with unresectable intrahepatic recurrence, TACE can help prolong the survival of patients, [31] which may be due to the rich blood supply of new tumors and the strong dependence of tumors on blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…This was not significantly different from the mean overall survival (4 months) of patients treated with symptomatic and supportive care. Studies have reported that HSCs are hypovascular tumors, [29] and TACE is a risk factor associated with poor prognosis. [30] For patients with unresectable intrahepatic recurrence, TACE can help prolong the survival of patients, [31] which may be due to the rich blood supply of new tumors and the strong dependence of tumors on blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Upper abdominal pain appeared gradually with enlargement of the tumor; the patient also demonstrated typical clinical manifestations. As there are no specific tumor markers for SHC, imaging is the mainstay for detection of the lesions ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, among the four lesions with hepatic surface retraction, three tumors lacked capsules and one had partial capsule, indicating that most of them were prone to invade peripheral regions owing to the lack of limitation of complete capsule. Furthermore, it should be noted that the differential diagnosis should also include liver metastases, liver abscess, scirrhous subtype of HCC and primary hepatic sarcoma, which all could present as “slow-in and and slow-out” enhancement pattern, with larger size, lobulated or wavy contours and infiltrative morphology in some cases [ 12 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%